AN EDITORIAL ABOUT ARCHITECTURE EDUCATION LIMITATION - Harsritanto, Bangun I R (MODUL, 2023)
On this Vol 23 no2, MODUL has published 5 scienteific articles. With compiling the information of all published articles, this editorial try to provide a resume using theory of architecture education limitation